Study on the Effect of Breeds on Physiochemical Parameters of Goat Milk at National Goat Research Program, Bandipur Tanahun Nepal - Dahal, Maheshwar; Kadel, Raju; Ghimire, Shivahari; Acharya, Buddhi Ram (Nepalese Journal of Agricultural Sciences, 2026)
This study analyzed breed-specific variations in milk composition among pure Saanen, pure Boer, and pure Khari goats at National Goat Research Program in Bandipur, Tanahun between March and May, 2018. Using a milk analyzer, we evaluated 96 Saanen, 12 Boer, and 12 Khari milk samples for protein, fat, SNF, lactose, and freezing point. Statistical analysis was performed using SPSS software with mean comparisons at a 0.01 significance level. The results revealed no significant differences (p>0.01) among the breeds for protein, lactose, SNF, and freezing point values. However, pure Boer goats showed significantly higher fat content (7.96±0.48%) compared to both Saanen and Khari breeds (p